Death by a Thousand Cuts: an archaeological assessment of souveniring and salvage on the Australian cruiser HMAS Perth (I). (31st July 2018) - Hosty, Kieran; Hunter, James; Adhityatama, Shinatria
Abstract: In 2014, the Australian National Maritime Museum (ANMM) received reports from recreational divers that the shipwreck site of HMAS Perth (I) was being systematically salvaged by commercial divers. After extensive discussions with Indonesian Government departments and agencies the ANMM led the first Australian/Indonesian remote sensing survey of Perth in December 2016. This was followed by an in‐water survey in May 2017. These investigations revealed Perth has been devastated by systematic, large‐scale unauthorized salvage. Following the survey, ANMM and its Indonesian research partner Pusat Penelitian Arkeologi Nasional (ARKENAS), working in conjunction with the Royal Australian Navy and Australian Department of Foreign Affairs and Trade, successfully lobbied the Indonesian Government to have the site declared Indonesia's first Marine Protected Area.